Effect of submucosal application of tramadol on postoperative pain after third molar surgery - BAYRAM, FERİT; GÖÇMEN, GÖKHAN; GARİP, HASAN; GÖKER, MEHMET KAMİL; GÖNÜL, ONUR (BIOMED CENTRAL LTD, 2015)
The aim of this study was to evaluate the effectiveness of submucosal application of tramadol, for acute postoperative facial pain, following the extraction of impacted third molar teeth. This prospective, double-blind, randomised placebo-controlled study included 60 ASA I-II patients undergoing impacted third molar surgery under local anaesthesia. Following the surgical procedure, patients were randomly divided into two groups; group T (1 mg/kg tramadol) and group S (2-mL saline). Treatments were applied submucosally after surgery. Pain after extraction was evaluated using a visual analogue scale (VAS) 0.5, 1, 2, 4, 6, 12, 24, and 48 h postoperatively. The time at which the first analgesic drug was taken, the total analgesic dose used, and adverse tissue reactions were also evaluated. In group T, postoperative VAS scores were significantly lower compared to that in group S (p < 0.05). This study demonstrated that post-operative submucosal application of tramadol is an effective method for reducing acute post-operative facial pain after impacted third molar surgery.
Keywords: Tramadol; Third molar surgery; Postoperative analgesia; MANDIBULAR 3RD-MOLAR; EFFICACY